Multiple Subconjunctival “Tahitian Pearls” - Anushri Godbole; Gaurav Kamble; Amit S. Nene; Sheetal Divate; Onkar H. Pirdankar (Delhi Journal of Ophthalmology)
The present report aims to describe the anterior optical coherence tomography findings of subconjunctival silicone oil bubbles in a 27-year-old female who had undergone retina surgery.